Traumatic Brain Injury within Domestic Relationships: Complications, Consequences and Contributing Factors. Issue 6 (3rd July 2019) - Baxter, Kathleen; Hellewell, Sarah C.
ABSTRACT: Traumatic brain injury (TBI) resulting from episodes of domestic violence (DV) is a serious yet greatly underreported issue. Head injuries arising in these circumstances are often concussive or sub-concussive in nature, and are unlikely to be isolated incidents, with victims frequently suffering repetitive TBIs over time. Although men may also be victims of DV, women and children are most at risk of DV via intimate partners and parents, respectively. Due to the complexities of these interpersonal relationships, victims of DV are not always able to receive appropriate clinical diagnoses, care or follow-up after TBI. TBI arising from DV is also likely to occur in a complex milieu of fear, anxiety and depression, the physical and psychological consequences of which may worsen or perpetuate the pathology of TBI. This review examines the complexities of TBI arising from DV from several perspectives, with focus on three pertinent and interrelated topics: 1) pathobiology and complications of single and repetitive TBI, encompassing direct neural consequences, inflammation and hormonal changes; 2) behavioral, cognitive and psychosocial consequences of TBI; and 3) contributing factors to TBI and complications, including strategies to increase clinician recognition of TBI in DV patients, and programs and policies in place in Australia and abroad to decrease rates of offending.